2022
DOI: 10.1371/journal.pone.0267739
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of household’s waste disposal practices and willingness to participate in reducing the flow of plastics into the ocean: Evidence from coastal city of Lagos Nigeria

Abstract: Marine plastic pollution is a critical environmental challenge facing policymakers globally. To reduce marine plastic pollution by engaging the people, this study estimated the determinants of waste disposal approach by households, their willingness to participate in road gutters/drainage channels cleanup program and the number of man-days they are willing to contribute. The study used a total of 600 households drawn from 30 enumeration areas. A semi-structured questionnaire was employed in data collection. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The study by Cheng et al showed that knowledge has a positive effect on waste separation behaviour and that women participate more in waste separation [ 51 ]. The results of two studies have shown that women are more likely to separate their waste [ 52 , 53 ]. The study by Aguilar et al showed that environmental education has a positive effect on people's attitudes and improves their waste-sorting behaviour [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Cheng et al showed that knowledge has a positive effect on waste separation behaviour and that women participate more in waste separation [ 51 ]. The results of two studies have shown that women are more likely to separate their waste [ 52 , 53 ]. The study by Aguilar et al showed that environmental education has a positive effect on people's attitudes and improves their waste-sorting behaviour [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, plastic consumption is much lower than other Western or developed nations, but this is projected to increase significantly in the coming years (Ayeleru et al, 2020; Babayemi et al, 2019; Sadan and De Kock, 2021). Plastic policies, such as bans and taxes, have been implemented across the continent with varying degrees of success, but there remains a need for projects to tackle an ongoing mismanaged waste problem (Chukwuone et al, 2022; Dumbili and Henderson, 2020). Studies have found the informal waste sector to be a large source of jobs and income and plastic management (Barford and Ahmad, 2021; Bening et al, 2021; Kaza et al, 2018).…”
Section: Case Study Applicationmentioning
confidence: 99%
“…Regulatory tools are critical as they provide guidance, support and investments; however governance strategies are implemented gradually and do not immediately remediate inadequate waste management. In the meantime, services are being provided by bottom-up actors and strengthening and scaling these initiatives can help reach global waste management goals (Chukwuone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mengurangi polusi sampah plastik butuh kerjasama dari semua individu dengan pendekatan pembuangan sampah rumah tangga yang terpadu dengan tepat serta mengatasinya melalui program pembersihan semua saluran drainase (Chukwuone et al, 2022). Untuk mengatasi hal tersebut juga tentunya harus dibuatkan sebuah tempat yang dapat menampung limbah.…”
Section: Pendahuluanunclassified